Pendidikan Kewirausahaan di Pondok Pesantren Tarekat Idrisiyyah di Tasikmalaya Jawa Barat - Rasidin, Mhd.; Busni, Darti; Afrilia, Kesi (Pusdiklat Tenaga Teknis Pendidikan dan Keagamaan, 2023)
The Tariqa and Islam in general are not against worldly and materialistic pursuits. Even in Islam, there are strict rules governing matters related to economic life or what is called muamalah. The four pillars of the Idrisiyyah congregation which are growing rapidly in the Tasikmalaya region of West Java Province are the basis for the teachings of asceticism in the growth and empowerment of the Islamic economy. This article discusses entrepreneurship education in tarekat Islamic boarding schools with a study of the Idrisiyyah tarekat doctrine in developing the congregation’s economy in Tasikmalaya, West Java. This article uses case studies and qualitative research methodology. Primary data sources are obtained from interviews, observation, and documentation techniques, while secondary sources come from books, journals, theses, and articles that are relevant to the research topic. The research was conducted from March 14 to March 30 2023 at the Idrisiyyah Tasikmalaya Islamic Boarding School, West Java. Data analysis techniques utilize the methods popularized by the Miles and Huberman models, namely data collection, data reduction, data presentation, and drawing conclusions. The findings show that the Sufi concept and doctrine of the Idrisiyyah tarekat serve as the basis for the entrepreneurship education given at the Idrisiyyah Tasikmalaya Islamic Boarding School. The history of the involvement of the Prophet Muhammad in the field of trade is the cornerstone of the economic success of the Idrisiyyah order. In addition, there are principles that must be adhered to in living an economic life in the Idrisiyyah order, namely the principles of divinity, scripture, worship, agreement, imamate and leadership. (Tarekat dan Islam pada umumnya tidak bertentangan dengan pengejaran duniawi dan materialistis. Bahkan dalam Islam, terdapat peraturan ketat yang mengatur hal-hal yang berkaitan dengan kehidupan ekonomi atau yang disebut dengan muamalah. Empat pilar tarekat Idrisiyyah yang berkembang pesat di wilayah Tasikmalaya Provinsi Jawa Barat menjadi landasan ajaran zuhud dalam pertumbuhan dan pemberdayaan ekonomi Islam. Artikel ini membahas pendidikan kewirausahaan di pondok pesantren tarekat dengan studi atas doktrin tarekat Idrisiyyah dalam pengembangan ekonomi jamaah di Tasikmalaya Jawa Barat. Artikel ini menggunakan studi kasus dan metodologi penelitian kualitatif. Sumber data primer didapat dari wawancara, observasi, dan dokumentasi, sedangkan sumber sekunder berasal dari buku, jurnal, tesis, dan artikel yang relevan dengan topik penelitian. Penelitian dilaksanakan pada tanggal 14 Maret sampai dengan 30 Maret 2023 di Pesantren Idrisiyyah Tasikmalaya Jawa Barat. Teknis analisis data memanfaatkan metode yang dipopulerkan oleh model Miles dan Huberman, yaitu pengumpulan data, reduksi data, penyajian data, dan penyusunan kesimpulan. Temuan menunjukkan bahwa konsep sufi dan doktrin tarekat Idrisiyyah berfungsi sebagai dasar untuk pendidikan kewirausahaan yang diberikan di Pesantren Idrisiyyah Tasikmalaya. Sejarah mengenai keterlibatan Nabi Muhammad SAW dalam bidang perdagangan merupakan landasan keberhasilan ekonomi tarekat Idrisiyyah. Selain itu ada prinsip yang harus dipegang dalam menjalani kehidupan ekonomi di tarekat Idrisiyyah yaitu prinsip ketuhanan, kitabiah, peribadatan, perjanjian, imamah dan kepemimpinan.)